Socio-Psychological Characteristics Of Destructive Motivation In The Field Of Social Services - Gyulambaryan, Nona (Զանգակ հրատ.)
The article presents the social-psychological characteristics of the phenomenon of destructive motivation in the field of social services. The general characterization of the mental states of the persons – recipients of the social services is given. The research question is that the socio-psychological characteristic of the personality represents a set of issues relating to the relationship of the individual with the environment and the mental states of the individual caused by them. Mental states occupy a special place in a person’s life since they directly regulate human behavior and activity. The purpose of the article is to interpret destructive motivation as a state of low expectations, self-isolation, the behavioral strategy of avoidance and adaptive disorders. The scientific innovation of the article is that mental states can be considered as a result of the level of psychological stability and determining its factor. According to the purpose, the structure of the article is constructed, and the main tasks are revealed to present the perspectives of further investigation of the issue of destructive motivation.
Keywords: Psychology